ENTRY MODE DECISION MAKING PROCESS - Avadhanula, Ramesh Kumar (My University, 2011)
Decision making is the important process in formulating the entry mode strategies. The main objective of this study is to explore the entry mode decision making process a firm entering in to new market. This study explains the entry mode decision making of the case company. In the theoretical part of this study firstly the strategic decision making is discussed. The next part of the theoretical part explains the various modes in strategic decision making. Furthermore the theoretical part discusses about the decision making in the context of entry mode and as well as in the context of entry mode choice approaches. The later part of the theory explores the stages that are involved in the entry mode decision making process. At final the theoretical part explains the importance of emerging markets. The empirical part of the study is done through the face to face interview with the case company. Moreover, the case company’s annual reports, publications and the internet pages were also used in the empirical part of the study. The empirical results of the study explains three stages in the entry decision making process of the case company which are market and need identification, entry mode data collection and decision making stage. It is revealed from the results that the case company’s decision making process is based on avoidance mode.
Keywords: Entry modes; Decision making; Strategy; Internationalization; Emerging markets.; fi=Markkinointi|en=Marketing|; fi=Master's Degree Programme in International Business|